Ethics without borders - Fisher, James E.; Guithues-Amrhein, Denise (London : NeilsonJournals Publishing, 2014)
John Berry, a risk manager for a U.S.-based pharmaceutical firm (Best Co.), is assigned additional responsibilities when his territory is expanded to include the South America region. When an employee in one of Best Co.'s South American manufacturing facilities dies in a work-related incident, John must determine an appropriate response. In a business context that is increasingly global, ethical decisions are further complicated by cultural differences. This case considers the factors influencing John as he weighs his options on how to resolve this incident. The case further considers how cultural differences coupled with John's limited cross-cultural sensitivities and personal viewpoint might inevitably skew his judgment. San Luis, the disguised name for this South American locale, is less litigious than John's home country, the U.S. In light of these differences, the case raises a number of ethical questions. For example, how should an international corporation compensate an employee's family for the employee's work-related death - if at all? Are John's own cultural limitations preventing him from doing the right thing?
Originally Published InFisher, J. E., & Guithues-Amrhein, D. (2014). Ethics without borders. Journal of Business Ethics Education, 11(1), 325-330. JBEE11-0CS2.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Berry, John; Best Co; Industrial accidents; Business ethics; Employers' liability